EEG classification for the detection of mental states - Vézard, Laurent; Legrand, Pierrick; Chavent, Marie; Faïta-Aïnseba, Frédérique; Trujillo, Leonardo (Applied soft computing, 2015)
[Display omitted] •A method able to automatically determine mental states of alertness is developed.•A complete protocol of EEG data acquisition is detailed.•Analysis of the Contingent Negative Variation is used to validate the EEG data.•Best compromise number of electrodes/quality of the solution: 9 electrodes.•Provides an accurate and fast prediction of the alertness of an unseen individual. The objective of the present work is to develop a method that is able to automatically determine mental states of vigilance; i.e., a person's state of alertness. Such a task is relevant to diverse domains, where a person is expected or required to be in a particular state of mind. For instance, pilots and medical staff are expected to be in a highly alert state and the proposed method could help to detect possible deviations from this expected state. This work poses a binary classification problem where the goal is to distinguish between a “relaxed” state and a baseline state (“normal”) from the study of electroencephalographic signals (EEG) collected with a small number of electrodes. The EEG of 58 subjects in the two alertness states (116 records) were collected via a cap with 58 electrodes. After a data validation step, 19 subjects were retained for further analysis. A genetic algorithm was used to select a subset of electrodes. Common spatial pattern (CSP) coupled to linear discriminant analysis (LDA) was used to build a decision rule and thus predict the alertness of the subjects. Different subset sizes were investigated and the best compromise between the number of selected electrodes and the quality of the solution was obtained by considering 9 electrodes. Even if the present approach is costly in computation time (GA search), it allows to construct a decision rule that provides an accurate and fast prediction of the alertness state of an unseen individual.